Intellectual Property Commercialization Policy to Expand Financing Options for Indonesian Creative Economy Businesses - Fitria Mahmudah; Mohammad Benny Alexandri; Yogi Suprayogi Sugandi (Eduvest - Journal of Universal Studies, 2024)
This study aims to develop alternate strategies for completing the creative economy Intellectual Property collateral financing policy so that it may be implemented in Indonesia. The methods used descriptive qualitative research with SWOT analysis to analyze the implementation of Intellectual Property-based financing schemes' supporting and inhibiting factors. The preparation of alternative strategies based on the SWOT matrix produces nine strategies. The nine alternative strategies produced were evaluated and tested using four practical policy analysis criteria: Effectiveness, Efficiency, Legality, and Administrative Robustness. Three primary recommendations emerged from testing alternative approaches: first, a plan to fortify industry regulations related to financial services, which will serve as a model for financial institutions implementing credit provisions based on Intellectual Property collateral and expediting the realization of financing products backed by Intellectual Property Rights. Second, a plan to standard Intellectual Property valuation formula or economic value of Intellectual Property and establish an ecosystem for the Intellectual Property market to promote more consistent Intellectual Property valuations and third, managing credit risk through joint ventures with insurance companies, the debtor will pay the insurance costs that allow the Bank or Financial Institutions to transfer risks to third parties if the Intellectual Property value declines.